Neuroticism and momentary differentiation of positive and negative affect. (March 2015) - Skalina, Lauren M.; Gunthert, Kathleen C.; Ahrens, Anthony H.; Wenze, Susan J.
Highlights: We examined how neuroticism impacts affective differentiation in three samples of young adults. We found that neuroticism moderates the within-person relationship between PA and NA. Those higher in neuroticism experience less affective differentiation. This effect was not moderated or mediated by life stress. This finding held across three sizable samples ( n  = 126, n  = 102, and n  = 120). Abstract: Affective differentiation is the degree to which positive affect (PA) and negative affect (NA) are uncorrelated. The dynamic model of affect (Zautra, Potter, & Reich, 1997) posits that the link between PA and NA should be stronger when stress is high. Because neuroticism relates to more negative everyday stress perceptions and therefore higher daily stress, we hypothesized that neuroticism should be associated with lower affective differentiation on a daily basis. We examined how neuroticism impacts momentary affective differentiation in undergraduate students ( n  = 126) using an experience sampling design with mood monitored four times daily for one week. We found that neuroticism moderates the within-person relationship between PA and NA: those who are higher in neuroticism experience less affective differentiation. This effect was not mediated or moderated by recent major life stress. We replicated the main finding in two subsequent samples ( n  = 102 and n  = 120, respectively), and thus present the first large set of studies to demonstrate consistently that neuroticism moderates the within-person link between PA and NA.